Preparing effective special education teachers - Mamlin, Nancy (New York : Guilford Press, 2012)
'What tools are in the toolkit of an excellent special educator, and how can teacher preparation programs provide these tools in the most efficient, effective way possible? This practical, clearly written book is grounded in current research and policy as well as the author's extensive experience as a teacher educator. It identifies what special education teachers need to know to work competently with students with a wide variety of learning challenges and disabilities. Chapters present specific guidelines for helping teacher candidates build critical skills for instruction and assessment, get the most out of field placements, and collaborate successfully with other school personnel and with parents. Subject Areas/Keywords: assessments, curriculum, disabilities, exceptional children, field work, IEPs, inclusion, instruction, learning, lessons, professional development, special education, special needs, standards, students, teacher preparation programs, teacher training, teachers, teaching Audience: Teacher educators in special education, graduate students preparing to be teacher educators, and school district personnel who provide staff development for special education teachers'--
Machine generated contents note: 1. A Framework for Teacher Education in Special Education: Teacher Education Matters2. Who Are the Candidates?3. Field Experiences: A'Must Have'4. The'Job' of a Special Education Teacher5. Special Education Knowledge Base6. Assessment: Have We Met Our Goals?7. Preparing Excellent Special EducatorsList of AbbreviationsAnnotated BibliographyAppendix A. Council for Exceptional Children Standards for Professional PracticeAppendix B. Council for Exceptional Children Personnel Preparation StandardsAppendix C. Association of Teacher Educators Standards for Teacher EducatorsAppendix D. Council for Exceptional Children Code of Ethics.
Includes bibliographical references and index.
Keywords: Special education teachers -- Training of -- United States; Special education -- Study and teaching -- United States